Capacity of enforcers and level of enforcement of the Tobacco Control Act 2015 in Kampala, Uganda. - Hafsa Lukwata; David Musoke; Solomon T Wafula; John C Ssempebwa (Public Library of Science (PLoS), 2023)
Tobacco use is a leading cause of preventable deaths worldwide. Uganda enacted the Tobacco Control Act (TCA) 2015 to domesticate implementation of the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) regulations. This study assessed the capacity to enforce the TCA and associated factors, as well as the level and barriers to its enforcement in Kampala, Uganda. A cross-sectional study using both quantitative and qualitative methods was employed. A structured questionnaire was used for quantitative data collection, and a WHO adapted capacity assessment open-ended guide was used for key informant interviews. Multivariable logistic regression was used to obtain odds ratios and 95% confidence intervals for the independent predictors for capacity to enforce the TCA. A total of 162 respondents from 5 institutions and six key informants were involved in the study. Findings established that only 23% (37/162) of the enforcers had the capacity to enforce the TCA. Male enforcers [OR = 0.16, 95% CI (0.05-0.55)], those who did not know when the law was enacted [OR = 0.19, 95% CI (0.07-0.52)], those with no plans to enforce the law [OR = 0.22, 95% CI (0.05-0.93)], and older enforcers (aged 31-40 years) [OR = 0.27, 95% CI (0.09-0.81)] were less likely to have the capacity to enforce the TCA. The level of enforcement of the TCA was mainly low to moderate for most of the institutions mandated to enforce it. Lack of knowledge about the law amongst the enforcers and general public, and inadequate funds were reported as major barriers to enforcement of the TCA. The capacity to enforce the TCA in Kampala was low. There is potential to enhance the capacity of enforcers through further dissemination of the Act, as well as sensitization of enforcers, institutional managers, and the general public about the legislation.